The Role of Left Ventricular Mass Index-adjusted Ejection Fraction in Early Detection of Diabetic Cardiomyopathy and its Association with Major Adverse Cardiovascular Events - Pichakacheri Sureshkumar; Sidharth S. Kumar; Rajesh Gopalan Nair; P. K. Asokan (Journal of Indian College of Cardiology)
Background: Diabetic cardiomyopathy (DbCM) serves as a specific risk marker for cardiac failure and elevated major adverse cardiovascular events (MACE) in individuals with type 2 diabetes mellitus (DM). However, diagnosing early DbCM cases remains challenging due to the lack of specific parameters, especially in primary care settings equipped only with conventional echocardiography machines. Aim: The aim of this study was to investigate the role of left ventricular mass index-adjusted ejection fraction (LVMI-EF) on the assessment of early DbCM and its relationship with MACE in patients with type 2 DM. Materials and Methods: Echocardiographic data from 419 patients were analyzed, calculated their LVMI-EF, and compared against measured left ventricular ejection fraction (LVEF). Patients with lower LVMI-EF were considered to have DbCM. Subsequently, all the patients were followed up for a mean period of 2 years. Results: After adjusting for LVMI, LVEF in the normal range decreased by 12%(p=<0.001), while there was an increase of mild, moderate and severe left ventricular systolic dysfunction categories by 7.87% (p=<0.001),1.8% (p=0.5614)and 1.4% (p=0.5614) respectively. Kaplan–Meier survival analysis revealed a significantly higher risk of MACE in patients with lower LVMI-EF (presumed to have DbCM; P = 0.001; odds ratio = 7.1505; 95% confidence interval: 3.1644–16.1576). Conclusion: LVMI adjustment of LVEF is a valuable tool for identifying DbCM, particularly in its early stages, and LVMI-EF serves as a prognostic indicator for MACE in type 2 DM patients.